Security threats to privacy data of Malaysian youth’s: online transaction and communication - Shariffah Mamat,; Wan Amizah Wan Mahmud,; Arina Anis Azlan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The new norms during the COVID-19 pandemic contributed to the increased usage of the online medium. The International Labour Organization (ILO) reports that millions of people were forced to stay at home during difficult situations (2020). Both the government and corporate sectors are changing the landscape of their services to online services. Apart from its benefits, the rapid adoption of technology also increases the risk of data breaches among individuals' personal information. This article focuses on the intention factor as a motivation to protect the security of personal data among the youth. A total of 535 respondents in the range of 19 to 30 years old from Putrajaya and Cyberjaya. They are randomly selected using a multistage cluster sampling method. A set of questionnaires were distributed online during the Movement Control Order (MCO) that hit all over the world including Malaysia. To analyse factors affecting the Malaysian youth in protecting the security of personal data the multiple linear regression analysis was applied. This article reports the intention factor has a dominant influence in motivating Malaysian youth to protect the security of their data. Additionally, findings showed that family connection and online banking transactions as the main factors in using online compared to other motives measured in this study. Therefore, Malaysian youths should be given the knowledge and awareness to keep on vigilant and protect their data security. Their motivations need to be nurtured to ensure that Malaysian youth’s personal data remain protected even if they are actively interacting online.